Pomen človekovega dostojanstva v zdravstveni negi - Šmitek, Jana (Obzornik zdravstvene nege, 2006)
Human dignity is an abstract concept which needs to be clarified when expecting its efficient use in nursing practice. Wide general explanation of the concept and its further meaning related to practical use in nursing care is presented in the article. The author conducted a qualitative research amongSlovenian nurses and nursing technicians. On the basis of open end questions she discovered the extent of modes of patient''s dignity respect and also the extent of undignified situations perceived in practice. An analysis of data presents a wide range of positive attitudes that preserve or promote patient''s dignity as much as numerous practical experiences of counter-evidence.
Keywords: ankete; Bolnik, pravice; bolniki; Človekove pravice; dostojanstvo; Human Rights; Medicinska sestra-bolnik, odnosi; Nurse-Patient Relations; Nursing Care; Patient Advocacy; Questionnaires; Zdravstvena nega